Kansyore Fisher-Hunter-Gatherers Abandoned the Northeastern Lake Victoria Shoreline during an Arid Period in the Middle Holocene: A Reconsideration of Dates from Western Kenya with New Radiometric and Faunal Evidence from the Namundiri A Shell Midden, Eastern Uganda - Jones, Mica B; Ruth, Tibesasa (Journal of African Ar chaeology, 2022)
Kansyore pottery-using groups of the northeastern Lake Victoria Basin represent one of only a few examples of ‘complex’ hunter-gatherers in Africa. Archaeologists link evidence of specialized fishing, a seasonal land-use cycle between lake and riverine sites, and intensive investment in ceramic production to behavioral complexity after 9 thousand years ago (ka). However, a gap in the Kansyore radiocarbon record of the region between ~7 and 4.4 cal ka limits explanations of when and why social and economic changes occurred. This study provides the first evidence of lakeshore occupation during this temporal break at the only well-studied Kansyore site in eastern Uganda, Namundiri A. Within the context of other sites in nearby western Kenya, radiometric and faunal data from the site indicate a move from the lake to a greater reliance on riverine habitats with middle Holocene aridity ~5–4 cal ka and the arrival of food producers to the region after ~3 cal ka.